124k views
1 vote
Confirm that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x.

f(x) = x-8/x+7 and g(x) = -7x-8/x-1

User MicroVirus
by
5.2k points

1 Answer

0 votes
f(g(x)) = [(-7x-8)/(x-1) - 8} / [(-7x - 8)/(x-1) + 7] =

[(-7x - 8 - 8(x-1)) / (x-1)] / [(-7x - 8 + 7(x-1)) / (x-1)] = (-15x) / (-15) = x.

g(f(x)) = [-7*(x-8)/(x+7) - 8] / [(x-8)/(x+7) - 1] =

[(-7x + 56 -8*(x+7)) / (x+7)] / [(x - 8 - (x + 7)) / (x+7)] = (-15x) / (-15) = x.

So since f(g(x)) = g(f(x)) = x we can conclude that f and g are inverses.
User Zhun Chen
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.